Ismail Al-Zain's Fatwa on Tajdīd al-Nikāh: Legal and Social Analysis of Remarriage Practices at KUA Walenrang in Luwu Regency - Desrianti, Desrianti; Ridwan, Muhammad Saleh; Qayyum, Rahman; Nusair, Abuyamen (MUI Sulawesi Selatan, 2024)
This study examines Ismail Al-Zain's fatwa on tajdīd al-nikāh and its relevance to remarriage practices at the Office of Religious Affairs (KUA) in Walenrang District, Luwu Regency, particularly among serial marriage perpetrators requiring official marriage registration. The research employs a field research method, combining a phenomenological approach to explore individual experiences with tajdīd al-nikāh and a normative juridical approach to analyze the issue through Islamic law, including the Qur'an, hadith, fiqh rules, and scholars' opinions. The findings reveal that while Ismail Al-Zain's fatwa permits tajdīd al-nikāh as jawāz (allowed), it should be avoided unless critically necessary. At the KUA of Walenrang, tajdīd al-nikāh is implemented not only to fulfill marriage registration requirements but also to address doubts about the validity of harmony and conditions in serial marriages. This practice is more accurately termed i'ādah al-nikāh, aiming to ensure compliance with Islamic legal requirements and resolve ambiguities associated with serial marriage legality. This study offers original insights into the practical and legal nuances of tajdīd al-nikāh versus i'ādah al-nikāh in the context of marriage registration. The findings underscore the critical role of legal clarity in protecting the rights of spouses and children and preventing future disputes in family law. The research highlights the importance of ensuring correct and legal marriage processes to address legal and social challenges in contemporary Islamic family practices.